Cultivating Spiritual Intelligence: A Holistic Approach to Character Education for Prospective Nuns in RSCJ Community - Diwu, Yolanda Alina; Nurdin, Encep Syarief; Ganeswara, Ganjar Muhammad (Jurnal Educatio FKIP UNMA, 2024)
Responding to the Church's invitation and the increasingly rapid development of the times, this has greatly influenced the development of today's children, resulting in formation changes in the way of formation in each congregation. The aim of this research is: To know and identify a description of the character education model that brings spiritual values to life in the formation of RSCJ nuns. This research is a qualitative research. This research was conducted at the Congregation of the Sacred Heart of Jesus (RSCJ) in Bandung, West Java and Jakarta. The results of the research carried out are increased self-awareness and spiritual understanding. Intrapersonal intelligence-based character education at RSCJ develops deeper self-awareness in prospective nuns, facilitating a process of introspection that allows them to understand internal emotions, desires, strengths and weaknesses. This increase brings significant spiritual growth, creating a strong foundation for the development of a richer and more meaningful relationship with God. The conclusion of the research carried out is the Development of Spiritual Values with a focus on developing spiritual values such as love, honesty and empathy. This research contribution provides recommendations for prospective nuns to be taught to use introspection and self-awareness as tools to integrate these values into their behavior and decisions, forming a character that is in accordance with spiritual principles.